An assessment of dried fish danggit (siganus canaliculatus) industry in Bantayan Island, Cebu - Parcon, Samuel A. (Technology Management Center, 2012)
The Philippines is now supplying around 1.6 million tons of fish annually which form the basis of the fish processing industry in the country. About one third of its annual total catch is processed as salted, dried, smoked, fermented, frozen and canned products and as fish meal (Guevara 1978, p. 1). Bantayan Island, specifically, is known for its dried marine products particularly the white-spotted spine foot, locally known as danggit (Siganus canaliculatus), which is considered as a special delicacy. Many believe that the danggit from Bantayan Island is the best. In fact, the entire Cebu Province shares this recognition (Parcon et al 2009, p. 1). The current fish drying industry is known to the Philippine market yet is still unable to penetrate the international market, which can generate better income to the producers. This is primarily due to the poor quality of the dried products, which cannot comply with the international standards. It is beset with several challenges to meet market demand and standards. Drying and smoking and other fish processing methods, as practised in most fishing areas like Bantayan Island, are the traditional methods that have existed for years. There is a lack of modern processing technology and of trained manpower in fish processing, resulting to challenges in the compliance to food safety standards, extension of product shelf life, packaging and labeling designs, technology upgrading, product standardization, marketing, access to capital and even business management. However, steps are being taken by the Government to counteract these problems as the Department of Trade and Industry reported that exporting dried marine products has big potential. While the fish drying industry of Bantayan has always been part and parcel of the fishing industry of the island, only one comprehensive study has been conducted on the industry so far. This study was conducted by the Confederation of Scientific and Professional Organization (COSPO) in 2003-2004 to gauge the feasibility of establishing a common drying facility and use of mechanical drying system that will cater to a larger scale. The study showed that the current drying methods in Bantayan Island are generally unsanitary. Walk through surveys revealed unsanitary practices, e.g., presence of garbage near drying area, presence of flies, unkempt processing area and other unhygienic practices. It was further confirmed both by the processors and the Bureau of Food And Drugs that the colony forming unit per gram in the sample dried products were way beyond international standards. The study yielded the conclusion that establishment of a common drying facility and use of mechanical drying system that will cater to a larger scale is feasible. This was implemented among selected and willing processors in the Municipality of Santa Fe. The pilot project demonstrated the sanitary mechanical drying system and operation. Although no official monitoring or evaluation has been conducted on the implementation of the project, the success of the project lies on the consistent quality of its dried fish products after five years of operation with the Santa Fe LGU continually paying off its loan, even if in small increments, indicating that despite an increase of prices of mechanically dried fish products, these have a ready market. The Santa Fe experience is one proof that producing quality dried marine products already can be a lucrative business enterprise, given the support that the industry needs to penetrate the international market. This study is an attempt to continue the efforts that has been started by COSPO and currently being sustained by the Municipality of Santa Fe. This study on the "Assessment of Dried Fish Danggit (Siganus Canaliculatus) Industry in Bantayan Island, Cebu" is based on the premise that adoption of the Philippine National Standards for dried danggit to be able to pass the international standards. From there, it conducted an investigation on the drying methods currently being utilized by the industry and identified the technology innovation gaps that the industry is experiencing. These required a comprehensive look into the technoware of the drying methods as well as a broadbrush treatment of the humanware, orgaware and infoware dimensions of the industry. Mapping of the value chain of the industry was also created to determine the functions, operators and supporters and their interrelationships within the industry.